College Students’ Attitudes Towards Reading Dzongkha and Its Implications on Bhutan - Wangchuk, Chencho; Namgay, Kinley; Wangchuk, Nima (Bhutan Journal of Research and Development, 2023)
This study examined college students’ attitudes towards reading Dzongkha and the possible implications of the preferential choice of either English or Dzongkha as a language for reading may have on Bhutan. Using mixed-methods triangulation, the study examined college students’ attitudes toward reading Dzongkha. Data obtained from three data sources were merged and triangulated. Although the respondents showed a positive attitude towards reading Dzongkha, the majority of them, however, preferred English as a language for reading, which is deeply concerning for Bhutan. Based on the findings, the researchers have provided three recommendations, with the first being introducing additional but relevant Dzongkha modules for students pursuing higher degrees in English-medium colleges. Others include instituting mandatory DSTS test results for all opportunities and establishing Dzongkha medium preschools for preschoolers.